2021
DOI: 10.21203/rs.3.rs-306699/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Prevalence and Predictors of Fear of Childbirth Among Pregnant Chinese Women: a Hierarchical Regression Analysis

Abstract: Background: Fear of childbirth(FOC) runs through before, during and after pregnancy, which is harmful to both the pregnant woman and fetus. To identify the prevalence and predictors of FOC can help us generate strategies for alleviating women’s FOC.Methods: A cross-sectional study was conducted among a convenience sample of 646 pregnant women attending antenatal care at a subordinate hospital of an university in China. Data were collected using a Basic information form, Childbirth Attitude Questionnaire, Child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
(60 reference statements)
1
1
0
Order By: Relevance
“…Furthermore, the effects of discrepancy in resilience and FOC on psychological distress suggested that low resilience -high FOC leads to higher 10.3389/fpsyt.2022.1091042 psychological distress, while high resilience -low FOC promotes better mental health, indicating that resilience plays a significant role. These results were consistent with Huang's findings (30) that pregnant women with high resilience may actively use their own psychological resources to reduce fear and ultimately maintain better mental health.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the effects of discrepancy in resilience and FOC on psychological distress suggested that low resilience -high FOC leads to higher 10.3389/fpsyt.2022.1091042 psychological distress, while high resilience -low FOC promotes better mental health, indicating that resilience plays a significant role. These results were consistent with Huang's findings (30) that pregnant women with high resilience may actively use their own psychological resources to reduce fear and ultimately maintain better mental health.…”
Section: Discussionsupporting
confidence: 91%
“…Prior studies suggested that resilience has a protective effect on psychological distress during pregnancy (27)(28)(29). Furthermore, in a Chinese study involving 646 pregnant women has shown that resilience was negatively associated with FOC (30). Meanwhile, a recent research found that resilience served as a moderator between ACEs and psychological distress among pregnant women (22).…”
Section: Introductionmentioning
confidence: 99%